Nursing‐sensitive outcomes in adult inflammatory bowel disease: A systematic review. (10th January 2021) - Spagnuolo, Rocco; Corea, Alessandro; Napolitano, Daniele; Nisticò, Eleonora; Pagnotta, Raffaele; Pagliuso, Caterina; Schiavoni, Elisa; Turchini, Laura; Fiorino, Gionata; Radice, Simona; Armuzzi, Alessandro; Doldo, Patrizia
Abstract: Aims: To evaluate nursing activity through outcomes that are affected, provided, and/or influenced by nurses and defined as nursing‐sensitive outcomes in adult IBD patients. Design: Systematic review without meta‐analysis. Data Sources: PubMed, Embase, CINAHL, PsycINFO, and the Cochrane Library databases on August 2019. Review Methods: Peer‐reviewed articles published between 2000–2020 were reviewed. The outcome measures were contextualized and presented by OMERACT Filter 2.0. Results: Twenty‐four studies were included. Eighteen nursing‐sensitive outcomes were identified. These outcomes defined eight domains for health intervention, fitting into three core areas (resource use/economic impact, life impact, pathophysiological manifestations). Fifty‐three measurement instruments were identified. Conclusions: Through 53 measurement tools, with use of OMERACT framework, 18 nursing‐sensitive outcomes in the main 3 core areas were identified, highlighting the multidimensional role of nursing. Further insights are to be carried out to define nursing outcomes included in IBD nursing intervention studies. Impact: These results could serve as a cornerstone for further investigations and validation by a panel of experts to standardizing nursing activity in a multidisciplinary context.